Influence of the environment and production components on the protein content of green cowpea grain - Ribeiro Araújo, Linda; Barroso Neto, Antônio; Bertini, Cândida Hermínia; Lopes, Lineker; Gallão, Maria Izabel (Revista Ciência Agronômica, 2021)
The protein content of the cowpea has proved to be very variable, especially of the green grain. The aim of this study, therefore, was to obtain information on the influence of the environment and genetic variability on the total protein content (TPC) of green cowpea grain, as well as to evaluate the effects of production components on this variable. Sixteen cowpea genotypes were evaluated in two environments (Pentecoste and Acaraú) in the state of Ceará, in a simple factorial scheme (16 x 2) for eight production components and protein content. The grain was collected while still green (after filling was complete - stage R5) and protein quantification was carried out using the Bradford method. Path analysis was performed in order to identify possible relationships between the agronomic variables and the protein content. There was a different response from the genotypes for each environment and in the interaction between genotype and environment. In Pentecoste, the MNC00-303-09E strain was highlighted, with a TPC of 6.602%, while in Acaraú, the Paulistinha cultivar stood out with a TPC content of 15.154%. For the genotypes under evaluation, selection for total protein content should be made in Acaraú via direct selection of the green-pod-grain weight, 100-grain weight and green-pod weight, and in Pentecoste, via indirect selection of the green-pod weight and green-grain yield.